Pengaruh Quick Ratio, Debt to Equity Ratio, Net Profit Margin, dan Return On Investment Terhadap Pertumbuhan Laba Perusahaan Manufaktur (Subsektor Food and Beverage) Yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Dhining Putri Herianti; Nova Anggrainie (CV. ITTC INDONESIA, 2025)
The Food and Beverage subsector is one of the manufacturing company categories included in the consumer goods sector, and is currently experiencing significant growth. In an era of increasingly intense economic competition, companies are required to have strong competitiveness in order to survive and achieve their corporate goals. One of the main goals that every company wants to achieve is to maximize profits or earnings in each period. Therefore, financial statement analysis is needed to analyze, estimate profits, and make decisions regarding the profit growth that will be achieved by the company. This study aims to analyze the influence of the Quick Ratio, Debt to Equity Ratio, Net Profit Margin, and Return on Investment on Profit Growth in Manufacturing Companies in the Food and Beverage Subsector on the Indonesia Stock Exchange for the period 2019-2023. The data collection methods used are literature review and documentation. The analysis techniques used include descriptive statistical analysis, classical assumption tests (normality test, multicollinearity test, heteroskedasticity test, and autocorrelation test), multiple linear regression analysis, and hypothesis testing (F-test, t-test, and coefficient of determination). The results of the study indicate that the Debt to Equity Ratio and Return On Investment have a significant effect on the profit growth of manufacturing companies (food and beverage sub-sector) for the period 2019-2023. Meanwhile, the Quick Ratio and Net Profit Margin do not have a significant effect on the profit growth of manufacturing companies (food and beverage sub-sector) for the period 2019-2023. Translated with DeepL.com (free version)